2011
DOI: 10.1590/s0100-736x2011000800005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the frequency of antibodies against Babesia bovis and Babesia bigemina in cattle in southern Mozambique

Abstract: The study aimed to evaluate the risk factors associated with the frequency of IgG antibodies against Babesia bovis and B. bigemina in cattle in southern Mozambique. Eight hundred and nine serum samples were collected from cattle in three provinces namely Maputo, Gaza and Inhambane, and tested by indirect enzyme-linked immunosorbent assay (i-ELISA) to assess the humoral immune response towards B. bovis and B. bigemina. The chi-square test at 5% significance was used to determine whether there was an association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In the present study, no significant changes were observed among male and female cattle. These results were consistent with previous studies carried out in cattle [35,36].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, no significant changes were observed among male and female cattle. These results were consistent with previous studies carried out in cattle [35,36].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, piroplasmosis was detected in other provinces such as Gharbia [ 32 ], Port Said [ 33 ], Dakahlia [ 24 ], El-Wady El-Geded [ 3 , 4 ], Assiut and Kharga [ 34 ], and Qena [ 4 ]. Globally, theileriosis and babesiosis were detected in animals from different countries such as Pakistan [ 8 ], Brazil [ 9 ], Malaysia [ 10 ], and Mozambique [ 11 ]. For anaplasmosis, we detected Anaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, infection with Babesia causes significant economic costs in cattle, including death, production loss, lower feed intake and feed conversion efficiency, abortion, tick control losses, and disease prevention losses [ 9 , 10 ]. The most prevalent clinical manifestations linked with Babesia species infections in cattle include anemia, hemoglobinemia, pyrexia, and hemoglobinuria [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this finding, a lower prevalence was reported by Waktole et al 50 ; Wodajnew et al 51 , and Abdela et al 57 , who reported a prevalence of 3.38% ( B. bigemina ) and 0.26% ( B. bovis ) from Meki and Batu towns , 0.248% ( B. bigemina ) and 1.24% ( B. bovis ) from Assosa Ethiopia, and 9.8% ( B. bigemina ) and 2.2% ( B. bovis ) from Jimma town, respectively. However, a higher prevalence was reported by Tembue et al 58 ; Lemma et al 44 ; Rahman et al 41 ; Hamsho et al 4 , who reported a prevalence of 78.8% ( B. bovis ) and 76.0% ( B. bigemina ) from southern Mozambique , 60.8% ( B. bovis ) and 39% ( B. bigemina ) from Jimma town in southwestern Ethiopia, 17% ( B. bovis ) and 16% ( B. bigemina ) from Malaysia, and 9.9% ( B. bovis ) and 7.03% ( B. bigemina ) from Borana, respectively. Different investigations have also revealed that cattle infected with B. bovis remain carriers for long periods, while those infected with B. bigemina remain carriers for only a few months 13 , 56 .…”
Section: Discussionmentioning
confidence: 70%